Finite temperature spectral functions in the $O(N)$ model - Pawlowski, Jan M.; Strodthoff, Nils; Wink, Nicolas (Physical review, 2018)
We directly calculate spectral functions in the O(N) model at finite temperature within the framework of the functional renormalization group. Special emphasis is put on a fully numerical framework involving four-dimensional regulators preserving Euclidean O(4) and Minkowski Lorentz invariance, an important prerequisite for future applications. Pion and sigma meson spectral functions are calculated for a wide range of temperatures across the phase transition illustrating the applicability of the general framework for finite temperature applications. In addition, various aspects concerning the interplay between the Euclidean and real-time two-point function are discussed.
Gesehen am 10.02.2020